The art of the mini-deals: The invisible part of EU trade policy - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2023)
Trade policy is usually defined by the kinds of deals it can strike. Typically, the attention is focussed either on big multilateral trade rounds or on bilateral free trade agreements (FTAs). This policy brief goes beyond the conventional wisdom and sheds light on other trade agreements (trade mini-deals), which so far were less in the focus of EU trade experts and academics. The paper offers a preliminary assessment and a taxonomy of these trade mini-deals. The main takeaway is that there is a lot more going on than what meets the eye when it comes to EU trade policy. In reality, FTAs are just the tip of the trade policy iceberg. When taking a systematic look, it becomes apparent that FTAs are only one of the many trade policy instruments. Apart from FTAs, the EU has signed a much larger number of trade mini-deals that have, potentially, a significant impact on EU trade. The paper concludes with a short assessment of the role such mini-deals could play in the future, given the evolving nature of trade policy objectives and the growing complexity of international trade negotiations.
Keywords: 330